Biomass of elephant grass and leucaena for bioenergy production - Fernanda Aparecida Sales; Paulo Henrique Caramori; Wilian da Silva Ricce; Marco Aurélio Teixeira Costa; Geovanna Cristina Zaro (Semina: Ciências Agrárias, 2015)
The objective of this study was to evaluate the biomass production of elephant grass and leucaena in Paraná state, Brazil, for the generation of renewable energy. Two field studies were conducted in the municipality of Ibiporã (23° S, 51° 01?W). In the first study, the dry matter accumulation curves were calculated, with sampling at 30, 60, 90, 120, and 180 days after cultivation. The second study was conducted in a randomized complete block design with split plots. The total aboveground biomass production of elephant grass and leucaena was estimated in the main plot. Cutting times of 60 and 120 days after cultivation were evaluated in the subplots. The productivity of dry matter (kg.ha-1) was estimated using the biomass data. In addition, the potential production of energy from the burning of elephant grass biomass, and the potential production of total aboveground biomass and energy of elephant grass (in Paraná) was estimated using an agrometeorological model. Elephant grass can be potentially used as an alternative energy source. Leucaena has slow initial growth, and it must therefore be evaluated over a longer period in order to determine its potential. Simulation analyses of the capability of power generation, conducted based on the annual dry matter production, revealed that elephant grass could be an important source of renewable energy in the state of Paraná.